Green Marketing Drives Sustainability Via Innovation in Heritage Enterprises - Mudmainna; Salmah Sharon; Gracela Marisa Sanapang (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study examines the strategic role of green marketing in promoting business sustainability through the mediating effect of green innovation, utilizing Puing Tenane, a cultural heritage enterprise in Lamaholot, East Nusa Tenggara, as the focal case. Anchored in Dynamic Capabilities Theory, the research explores how externally oriented marketing efforts foster internal innovation and long-term sustainability in heritage-based enterprises. A quantitative design was adopted, using a structured questionnaire distributed to 150 respondents selected through snowball sampling across East Flores, Adonara, Solor, and Lembata. The data were analyzed using Structural Equation Modeling with the partial least squares (SEM-PLS) technique. The results reveal that green marketing enhances sustainability, both directly and indirectly, by stimulating innovation with in resource-constrained traditional businesses. These findings underscore the dual role of eco-marketing as both a communication strategy and driver of adaptive capability. Environmentally conscious branding and consumer education significantly impact operational transformation, particularly in enterprises rooted in local traditions. The study contributes to theoretical development by contextualizing capability-building in culturally embedded enterprises and emphasizing alignment between ecological practices and heritage values. It illustrates how sustainability-oriented marketing enhances stakeholder engagement and fosters innovation that improves market relevance and organizational resilience. Practically, this research offers insights for artisans, business leaders, and policymakers on embedding environmental values into heritage branding and production. Emphasis is placed on culturally grounded training, certification schemes, and digital storytelling that elevate sustainability narratives. The study invites further exploration into diverse heritage-based enterprises and provides a strategic pathway for achieving sustainability through innovation, culture, and ecological responsibility.